Inventory of Rare, Endangered and Threatened (RET) Plant Species in Maruthamalai Hills, Western Ghats of Tamilnadu, South India (Our Nature, 2015)
The present study deal with identification of rare, endanger and threatened plants in Maruthamalai Hills, part of Southern Western Ghats of Coimbatore District, Tamilnadu. In this investigation 30 rare, endangered and threatened (RET) plant species belongs to 15 families were identified and documented. Names of plants and RET category was gathered from IUCN annual reports and standard research articles. Enumerated plants were categorized in rare, endangered, endemic and threatened, species such as Caralluma bicolor, Terminalia arjuna, Ceropegia juncea, Rubia cordifolia, Celastrus paniculatus, Gloriosa suberpa, Gymnema sylvestres and so on. Finally it has been suggested that the RET medicinal plants are need to be proper conservation and management plans before it lost forever. DOI: http://dx.doi.org/10.3126/on.v12i1.12255Our Nature (2014), 12(1): 37-43.